Biochar and sewage sludge phosphorus fertilizer effects on phosphorus bioavailability and spinach ( Spinacia oleracea L.) yields under no-till system in semi-arid soils - Ugele Majaule; Oagile Dikinya; Bruno Glaser (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This field study evaluated the interactive effects of biochar (BC) and sewage sludge (SS) on P bioavailability and spinach yields for two seasons.Method Treatments were combinations of biochar (0, 2.5 and 5 Mg ha-1) and sewage sludge (0, 6 and 12 Mg ha-1), or mineral fertilizer (200, 28, and 18.9 kg ha-1), amended in a randomized complete block design to Luvisol and Cambisol.Results Significant (p < 0.05) yield increase of 53 and 65%, respectively occurred with increasing sole biochar doses on the Luvisol. Both applied alone and in combination with BC, the high rate of SS increased (p < 0.05) yields on the Luvisol over two seasons. Complimentary effects of 6SS+5BC on the Luvisol showed the highest yield increase for the study period. Co-application of amendments on the Cambisol decreased (p > 0.05) yields compared to sole amendments. Mehlich – 3 extractable P (M3-P) in control plots (CONT) increased between seasons, presumably due to P inputs from the irrigation water. Co-amendments on the Cambisol resulted in higher M3-P increase over mineral fertilizer than on the Luvisol in both seasons. Accumulation of M3-P in control plots confounded correlations between crop yields and available P. Higher P under BC compared to SS amended soils emphasize biochar capacity to capture P from irrigation water.Conclusion The results suggest that combined low rates of SS and BC can have significant effects on P availability and crop yields. Biochar enhanced plant P uptake, but decrease in yields with simultaneous increase in M3-P between seasons warrants further research.